PENDAMPINGAN INOVASI BONGGOL JAGUNG SEBAGAI MEDIA TANAM JAMUR DI KECAMATAN LENGKITI KABUPATEN OKU (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2023)
Corn is a plant that has great potential in Indonesia. Corn has a relatively high source ofcarbohydrates and calories (energy). Corn carbohydrate content ranks fourth after rice, sweetpotatoes and cassava. Corn (Zea mays) is one of the most important carbohydrate-producing foodcrops in the world, apart from wheat and rice. For residents of Central and South America, cornkernels are a staple food, as for some people in Africa and some people in Indonesia. At present,corn has also become an important component of animal feed. Another use is as a source of food oiland a base for cornstarch. And plants can also be used as compost for plants as it is taken from theleaves. The need for corn as a raw material for making cornstarch or corn flour always increasesevery year, because of the content of nutrients and vegetable protein in corn, making thisconfectionary very popular. of interest to many people. From the corn harvest and processed dryshelled corn, so many corn cobs are wasted and become garbage. This is of course a problem forcorn farmers in Mitra village. The solution given to partners is through training in processing corncobs as a mushroom growing medium. In addition to reducing the amount of corn post-harvestwaste, this service activity can also increase the income of corn farmers through mushroomcultivation. This activity gave rise to new businesses that could become partners' signatureflagship products, especially the Lengkiti District.